Synergistic Spin Transition between Spin Crossover and Spin‐Peierls‐like Singlet Formation in the Halogen‐Bonded Molecular Hybrid System: [Fe(Iqsal)2][Ni(dmit)2]⋅CH3CN⋅H2O1. (21st January 2014) - Fukuroi, Kappei; Takahashi, Kazuyuki; Mochida, Tomoyuki; Sakurai, Takahiro; Ohta, Hitoshi; Yamamoto, Takashi; Einaga, Yasuaki; Mori, Hatsumi
Abstract To introduce halogen‐bond interactions between a cation and an anion, a novel FeIII complex from iodine‐substituted ligands involving a paramagnetic nickel dithiolene anion was prepared and characterized. The compound exhibited the synergy between a spin‐crossover transition and a spin‐Peierls‐like singlet formation. The halogen‐bond interactions between the iodine and the sulfur atoms stabilized the paramagnetic state of π‐spins and played a crucial role in the synergistic magnetic transition between d‐ and π‐spins. In addition, the compound showed the light‐induced excited spin state trapping effect.